Measuring dimensional and morphological heat alterations of dismemberment-related toolmarks with an Optical Roughness-meter - Mata Tutor, Pilar; Villoria Rojas, Catherine; Márquez-Grant, Nicholas; Alvarez de Buergo Ballester, Mónica; Pérez-Ema, Natalia; Benito Sánchez, María (Springer, 2021)
This experimental study provides a further understanding of the post-burning nature of sharp force trauma. The main objective is to analyse the distortion that fire may inflict on the length, width, roughness, and floor shape morphology of toolmarks induced by four different implements. To this end, four fresh juvenile pig long bones were cut with a bread knife, a serrated knife, a butcher machete, and a saw. A total of 120 toolmarks were induced and the bone samples were thus burnt in a chamber furnace. The lesions were analysed with a 3D optical surface roughness metre before and after the burning process. Afterwards, descriptive statistics and correlation tests (Student’s t-test and analysis of variance) were performed. The results show that fire exposure can distort the signatures of sharp force trauma, but they remain recognisable and identifiable. The length decreased in size and the roughness increased in a consistent manner. The width did not vary for the saw, serrated knife, or machete toolmarks, while the bread knife lesions slightly shrunk. The floor shape morphology varied after burning, and this change became more noticeable for the three knives. It was also observed that the metrics of the serrated knife and machete cut marks showed no significant variations. Our results demonstrate that there is a variation in the toolmark characteristics after burning. This distortion is dependent on multiple factors that influence their dimensional and morphological changes, and the preservation of class features is directly reliant upon the weapon employed, the trauma caused, and the burning process conditions.
Keywords: Optical roughness metre; Heat-induced fractures; Fire; Sharp force trauma; Forensic anthropology